Long-term outcomes for different vaginal cuff closure techniques in robotic-assisted laparoscopic hysterectomy: A randomized controlled trial. (March 2017) - Tsafrir, Ziv; Palmer, Matthew; Dahlman, Marisa; Nawfal, A. Karim; Aoun, Joelle; Taylor, Andrew; Fisher, Jay; Theoharis, Evan; Eisenstein, David
Abstract: Objective: This randomized controlled trial aimed to evaluate the outcomes of different vaginal cuff closure techniques in robotic-assisted total laparoscopic hysterectomy. Study design: Ninety women undergoing robotic-assisted total laparoscopic hysterectomy for benign disease were randomized to three vaginal cuff closure techniques: running 2.0 V-Lock™ (Arm 1), 0 Vicryl™ figure-of-eight (Arm 2), and running 0 Vicryl™ with Lapra-Ty ® (Arm 3). Patients' records were reviewed for age, body mass index, smoking status and relevant co-morbidities. Operative times for vaginal closure and total length of surgery, estimated blood loss, and peri-operative complications were collected. Patients were evaluated at 2 and 6 weeks post-operatively, and interviewed 1 year following surgery by a telephone survey. Outcomes evaluated were vaginal cuff dehiscence, pain, dyspareunia and bleeding. Results: The study arms did not differ with respect to estimated blood loss (50 mL in each arm; p  = 0.34), median vaginal cuff closure time (14.5, 12 and 13 min, respectively; p  = 0.09) or readmission ( p  = 0.55). In the 1-year follow-up (54/90 respondents; 60%), there were no significant differences among study arms for vaginal bleeding, cuff infection or dyspareunia. Only women belonging to arm 3 reported vaginal pain (0%, 0% and 23%, respectively; p  = 0.01). No cases of vaginal cuff dehiscence were observed. Conclusions: The type of closure technique has no significant impact on patient outcomes. In the absence of a clear advantage of one technique over the others, the decision regarding the preferred method to close the vaginal cuff in robotic-assisted total laparoscopic hysterectomy should be based on surgeons' preference and cost effectiveness.